Simultaneous Activation of Erk1/2 and Akt Signaling is Critical for Formononetin-Induced Promotion of Endothelial Function - Wu, Jinjun; Kong, Muyan; Lou, Yanmei; Li, Leyan; Yang, Chunlin; Xu, Huifang; Cui, Yuqi; Hao, Hong; Liu, Zhenguo (Frontiers in Pharmacology, 2021)
Formononetin (FMNT) is a major bioactive compound from Astragalus membranaceus (Fisch.) Bunge, and has been widely used to treat conditions related to vascular insufficiency. However, the molecular mechanism for the therapeutic effect has not been well defined. This study aimed to investigate the effects and mechanism of FMNT on endothelial function. The potential targets and signaling pathways of FMNT in the setting of ischemia were predicted using network pharmacology analysis. Human umbilical vein endothelial cells (HUVECs) were used for the in vitro studies and C57BL/6 mice were used for in vivo experiments. The results of the network pharmacology analysis showed that multiple signaling molecules including MAPK and PI3K-Akt pathways could be involved in the pharmacological actions of FMNT against ischemic diseases. The experimental validation data showed that FMNT significantly promoted the growth, proliferation, migration and tube formation of HUVECs in association with activation of endothelial nitric oxide synthase (eNOS) and promotion of intracellular nitric oxide (NO) production. FMNT also markedly activated Erk1/2 and Akt signaling in HUVECs. The enhanced endothelial function by FMNT was abolished when the cells were pre-treated with eNOS inhibitor. FMNT-induced eNOS/NO activation, endothelial function and angiogenesis was also effectively attenuated when Erk1/2 or Akt signaling pathway was inhibited. In addition, FMNT significantly promoted wound healing in C57BL/6 mice associated with activation of Erk1/2 and Akt signaling. Enhanced wound healing by FMNT in mice was prevented when eNOS-, Erk1/2, or Akt-medicated signaling was inhibited. Moreover, when Akt signaling was inhibited in HUVECs, FMNT was still able to activate Erk1/2 signaling without promotion of endothelial function. Similarly, FMNT could activate Akt signaling with no change in endothelial function when Erk1/2 signaling was attenuated in HUVECs. Conclusively, the present study demonstrated that FMNT significantly enhanced endothelial function and promoted angiogenesis in vitro and in vivo through activating Erk1/2- and Akt-mediated eNOS/NO signaling pathway. The data also suggested that simultaneous activation of Erk1/2 and Akt signaling was required for FMNT-induced promotion of endothelial function. Results from the present study might provide support and evidence for the application of FMNT during the clinical treatment of conditions related to vascular insufficiency.